Long-term safety and effectiveness of canakinumab in patients with monogenic autoinflammatory diseases: results from the interim analysis of the RELIANCE registry - Kümmerle-Deschner, Jasmin; Kallinich, Tilmann; Henes, Joerg; Kortus-Götze, Birgit; Oommen, Prasad; Rech, Jürgen; Krickau, Tobias; Weller-Heinemann, Frank; Horneff, Gerd; Janda, Ales̆; Foeldvari, Ivan; Schuetz, Catharina; et al. (RMD Open, 2024)
Objective Interim analysis of the RELIANCE registry, an on-going, non-interventional, open-label, multicentre, prospective study evaluating the long-term safety, dosing regimens and effectiveness of canakinumab in patients with cryopyrin-associated periodic syndromes (CAPS), familial Mediterranean fever (FMF), tumour-necrosis factor receptor-associated periodic syndrome (TRAPS) or mevalonate-kinase deficiency (MKD)/hyperimmunoglobulin-D syndrome (HIDS). - Methods From September 2017 for patients with CAPS, and June 2018 for patients with FMF, TRAPS or MKD/HIDS, the registry enrolled paediatric (aged ≥2 years) and adult patients (aged ≥18 years) receiving canakinumab as part of their routine medical care. Safety, canakinumab dose, disease activity and quality of life outcome measures were evaluated at baseline and every 6 months until end of study visit. - Results At the analysis cut-off date (December 2020), 168 patients (91 CAPS, 54 FMF, 16 TRAPS and 7 MKD/HIDS) were enrolled. 85 (50.9%) patients were female and 72 (43.1%) were children (<18 years). The median patient age was 20.0 years (range 2.0-79.0 years). In the CAPS cohort, serious infections and serious adverse drug-reactions were more common in patients receiving higher than the recommended starting dose (SD) of canakinumab. A trend to receive >SD of canakinumab was observed in the pooled population. The majority of patients were reported as having either absent or mild/moderate disease activity (physician’s global assessment) from baseline to Month 30, with a stable proportion of patients (~70%) in remission under canakinumab treatment. Patient-reported disease activity (Visual Analogue Scale (VAS), Autoinflammatory Disease Activity Index), fatigue (VAS); markers of inflammation (C-reactive protein, serum amyloid A and erythrocyte sedimentation rate) remained well-controlled throughout. - Conclusion Data from this analysis confirm the long-term safety and effectiveness of canakinumab for the treatment of CAPS, FMF, TRAPS and MKD/HIDS.
Gesehen am 10.09.2024